2002
DOI: 10.1097/00024720-200210000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Single-Level Lumbar Spine Fusion: A Comparison of Anterior and Posterior Approaches

Abstract: This study is a retrospective review of 122 patients who underwent single-level lumbar spine fusion. The objectives were to directly compare perioperative morbidity and early results of single-level anterior interbody posterolateral intertransverse process lumbar spine fusion and to provide objective findings that may be useful in selecting surgical method. Lumbar spinal fusion is a well-recognized surgical treatment of intractable low back pain resulting from DDD or spondylolisthesis. Assessments of technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 27 publications
2
78
1
1
Order By: Relevance
“…Similarly, in a retrospective study of 1,014 consecutive patients undergoing posterior lumbar fusion, Takahashi et al identified female sex, older age as well as underlying degenerative spondylolisthesis and juxtafacet cysts as risk factors for incidental durotomy (12). Given the higher risk of blood loss associated with posterior approaches by both our study and the literature (2,4,5), preoperative identification of these risk factors might sway surgical decision-making in favor of an anterior approach. Similarly, demographic variables and underlying spinal pathology influence risk of intraoperative incidental durotomy.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Similarly, in a retrospective study of 1,014 consecutive patients undergoing posterior lumbar fusion, Takahashi et al identified female sex, older age as well as underlying degenerative spondylolisthesis and juxtafacet cysts as risk factors for incidental durotomy (12). Given the higher risk of blood loss associated with posterior approaches by both our study and the literature (2,4,5), preoperative identification of these risk factors might sway surgical decision-making in favor of an anterior approach. Similarly, demographic variables and underlying spinal pathology influence risk of intraoperative incidental durotomy.…”
Section: Discussionsupporting
confidence: 60%
“…Anterior approaches to lumbar fusion typically involve retroperitoneal or transperitoneal approaches performed in close proximity to the ureter, peritoneum, and iliac vessels (2,5). As a result, anterior approaches often involve ligation of sacral and lumbar segmental vessels and require splitting the abdominal muscles and retracting the iliac vessels, posing a higher risk of iliac vessel or presacral plexus damage and resultant hemorrhage compared to posterior approaches (2,5). Patient characteristics and operative variables that pose a higher risk for the different complications associated with each approach should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the improved devices to enhance a stabilization effect for single anterior surgery have been introduced and promoted the fusion rate. Current reports of open ALIF surgery have stated 93-100% of fusion success rate, which would be comparable with other fusion procedures 4,[18][19][20]25) . However, the present study showed about 84-86% of fusion success rate, which was relatively inferior to other results previously reported.…”
supporting
confidence: 52%
“…8 The follow-up period was 22 months for ALIF and 26 months for PLF. Fusion was assessed based on flexion-extension radiographs and CT scanning for ambiguous cases.…”
Section: Comparison Of Interbody Fusion and Plfmentioning
confidence: 99%